Application of Fuzzy AHP and COPRAS to Solve the Supplier Selection Problems - Mehdi Ajalli; Hossein Azimi; Abdolkarim Mohammadi Balani; Mahdi Rezaei (International Journal of Supply Chain Management, 2017)
Supply chain management (SCM) can be considered as a key component of competitive strategy to enhance organizational productivity, performance and profitability. In this paper, designed Questionnaires are sent to 5 professional experts in different departments of ABZARSAZI COMPANY in Iran. Proposed approach is based on Fuzzy Analytic Hierarchy Process (FAHP) and COPRAS (Complex Proportional Assessment) methods. The major purpose of this paper is ranking the suppliers of ABZARSAZI COMPANY by using a hybrid Fuzzy AHP and COPRAS approaches. Finally, results of this research, give an evaluation method for companies in order to help managers to identify and select the best suppliers.